Intercultural sensitivity and sociocultural adaptation among cabin attendants: direct, indirect and interaction effects on organizationally valued job outcomes - Lee, Gyehee; Karatepe, Osman M.; Kim, Jieun; Olorunsola, Victor Oluwafemi; Kim, Taegoo Terry (Emerald Group Publishing Ltd, 2025)
PurposeThis paper aimed to propose a research model that investigated job satisfaction (JSAT) and affective organizational commitment (AOC) as the serial mediators linking intercultural sensitivity (IS) to service-oriented organizational citizenship behavior (SOCB). It also explored sociocultural adaptation (SA) as a moderator of the influence of IS on JSAT.Design/methodology/approachData gathered from Korean cabin attendants employed at Middle Eastern airlines were utilized to gauge the aforementioned relationships via structural equation modeling.FindingsCabin attendants high on IS were satisfied with their jobs and therefore exhibited affective commitment to their airline company. Such employees in turn displayed heightened SOCB. SA strengthened the positive influence of IS on JSAT.Practical implicationsThe presence of interactive training, scenario-based simulations and cross-cultural communication exercises would enable cabin attendants to manage passengers with different cultural background successfully.Originality/valueThis empirical piece contributes to the pertinent literature by investigating the mechanisms underlying the link between IS and organizationally valued behavioral outcomes such as SOCB. It also enhances the understanding about SA which increases the positive impact of IS on JSAT.
Keywords: Cabin attendants; Intercultural sensitivity; Sociocultural adaptation; Job satisfaction; Affective organizational commitment; Service-oriented organizational citizenship behavior